Pilot multi‐centre randomised trial of the impact of pre‐operative focused cardiac ultrasound on mortality and morbidity in patients having surgery for femoral neck fractures (ECHONOF‐2 pilot). (11th December 2017) - Canty, D. J.; Heiberg, J.; Yang, Y.; Royse, A. G.; Margale, S.; Nanjappa, N.; Scott, D.; Maier, A.; Sessler, D. I.; Chuan, A.; Palmer, A.; Bucknill, A.; et al.
Summary: Hip fracture surgery is common, usually occurs in elderly patients who have multiple comorbidities, and is associated with high morbidity and mortality. Pre‐operative focused cardiac ultrasound can alter diagnosis and management, but its impact on outcome remains uncertain. This pilot study assessed feasibility and group separation for a proposed large randomised clinical trial of the impact of pre‐operative focused cardiac ultrasound on patient outcome after hip fracture surgery. Adult patients requiring hip fracture surgery in four teaching hospitals in Australia were randomly allocated to receive focused cardiac ultrasound before surgery or not. The primary composite outcome was any death, acute kidney injury, non‐fatal myocardial infarction, cerebrovascular accident, pulmonary embolism or cardiopulmonary arrest within 30 days of surgery. Of the 175 patients screened, 100 were included as trial participants (screening:recruitment ratio 1.7:1), 49 in the ultrasound group and 51 as controls. There was one protocol failure among those recruited. The primary composite outcome occurred in seven of the ultrasound group patients and 12 of the control group patients (relative group separation 39%). Death, acute kidney injury and cerebrovascular accident were recorded, but no cases of myocardial infarction, pulmonary embolism or cardiopulmonary arrest ocurred. Focused cardiac ultrasound altered the management of 17 participants, suggesting an effect mechanism. This pilot study demonstrated that enrolment and the protocol are feasible, that the primary composite outcome is appropriate, and that there is a treatment effect favouring focused cardiac ultrasound – and therefore supports a large randomised clinical trial.